1996
DOI: 10.1128/jb.178.15.4679-4687.1996
|View full text |Cite
|
Sign up to set email alerts
|

Iron is required to relieve inhibitory effects on NifL on transcriptional activation by NifA in Klebsiella pneumoniae

Abstract: In Klebsiella pneumoniae, products of the nitrogen fixation nifLA operon regulate transcription of the other nif operons. NifA activates transcription by 54 -holoenzyme. In vivo, NifL antagonizes the action of NifA under aerobic conditions or in the presence of combined nitrogen. In contrast to a previous report, we show that depletion of iron (Fe) from the growth medium with the chelating agent o-phenanthroline (20 M) mimics aerobiosis or combined nitrogen in giving rise to inhibition of NifA activity even un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
1
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(91 citation statements)
references
References 49 publications
1
87
1
2
Order By: Relevance
“…We recently showed that in vivo iron is specifically required for nif induction in K. pneumoniae, and additionally, that iron is not present in NifL (31,32). In order to examine whether oxygen is detected by a more general system rather than by NifL directly, we chose to examine the possible influence of Fnr on the nif induction in a heterologous E. coli system.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently showed that in vivo iron is specifically required for nif induction in K. pneumoniae, and additionally, that iron is not present in NifL (31,32). In order to examine whether oxygen is detected by a more general system rather than by NifL directly, we chose to examine the possible influence of Fnr on the nif induction in a heterologous E. coli system.…”
Section: Resultsmentioning
confidence: 99%
“…NifA-mediated activation of transcription from the nifHDK promoter in K. pneumoniae UN4495 and E. coli strains was monitored by measuring the differential rate of ␤-galactosidase synthesis during exponential growth (units per milliliter per optical density unit at 600 nm [OD 600 ]) (32). Inhibitory effects of NifL on NifA activity were assessed by virtue of a decrease in nifH expression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The N-terminal domain of NifL shows homology to the bat gene product of Halobacterium halobium, which is an oxygen-responsive activator, and contains one CysXXCys motif, similar to sequences involved in the binding of metal clusters in ferrodoxins and rubredoxins (3,15), which suggests the involvement of metals in the function of NifL. In fact, the involvement of iron in the function of NifL has been described (12,15,37). Recently, NifL from Azotobacter vinelandii has been reported as a flavoprotein redox sensor (13).…”
mentioning
confidence: 99%